2012
DOI: 10.1111/j.1439-0507.2012.02208.x
|View full text |Cite
|
Sign up to set email alerts
|

Practical considerations on current guidelines for the management of non‐neutropenic adult patients with candidaemia

Abstract: Recent guideline recommendations on the management of candidaemia provide valuable treatment guidance for routine clinical practice, but need to be interpreted in the light of the actual situation of the patient and the local epidemiology of fungal infections. Echinocandins emerge as the generally preferred primary treatment. Treatment should be initiated immediately after notification of a Candida-positive blood culture in all patients. Ambiguous issues include the definition of optimum duration of treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
(115 reference statements)
0
5
0
1
Order By: Relevance
“…Patients with catheter-related bloodstream infections (CRBSIs) were defined based on the current recommendations. [27][28][29][30][31] (i) Blood cultures from two body sites were positive for Candida species, along with clinical manifestations of yeast infection. (ii) Blood cultures and the catheter tip culture should be performed simultaneously, and both sites should be colonized with the same Candida species or the quantitative blood culture of the CVC tip sample showed a ≥5-fold greater CFU counts than the concurrent peripheral vein culture.…”
Section: Definitions and Microbiologic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with catheter-related bloodstream infections (CRBSIs) were defined based on the current recommendations. [27][28][29][30][31] (i) Blood cultures from two body sites were positive for Candida species, along with clinical manifestations of yeast infection. (ii) Blood cultures and the catheter tip culture should be performed simultaneously, and both sites should be colonized with the same Candida species or the quantitative blood culture of the CVC tip sample showed a ≥5-fold greater CFU counts than the concurrent peripheral vein culture.…”
Section: Definitions and Microbiologic Methodsmentioning
confidence: 99%
“…Patients with catheter‐related bloodstream infections (CRBSIs) were defined based on the current recommendations 27‐31 . (i) Blood cultures from two body sites were positive for Candida species, along with clinical manifestations of yeast infection.…”
Section: Methodsmentioning
confidence: 99%
“…This timing may vary depending on how often the blood cultures are taken and the fact that they are known to have slow turnaround times with median time to positivity of 2–3 days reaching 7 days in some situations. 18 , 19 Glockner at al., therefore, suggest to consider the timing of collection of the first negative blood culture as a starting point to initiate step down strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies have not found any correlation between duration of therapy and risk of long‐term complications, 52 therapy for 14 days appears to be necessary as well as sufficient (except for endocarditis) 53,54 . Protocols of several clinical trials recommend 14 days of therapy from the clearance of Candida from the bloodstream ie the first negative blood culture while on treatment 55 . Donowitz and Hendley found that 7 days of therapy with amphotericin was adequate in children with candidaemia 56 .…”
Section: Quality Indicatorsmentioning
confidence: 99%